MIDAS: a cloud platform for SOA testing as a service. (2015) - Francesco, Alberto De; Napoli, Claudia Di; Giordano, Maurizio; Ottaviano, Giuseppe; Perego, Raffaele; Tonellotto, Nicola
The increasing adoption of the service-oriented architecture approach makes software quality more challenging since traditional approaches for software testing are inadequate for SOA-based applications. The MIDAS platform is an integrated platform for SOA testing automation, designed and architected according to the SOA computing paradigm, and deployed on a public cloud infrastructure to tackle the variability in the computational resources necessary for testing SOA applications. It is available to end users as a testing as a service on a self-provisioning, pay-per-use, elastic basis. The cloud-based software architecture envisioned for the MIDAS platform and the strategies adopted for both its development, and its deployment on the target cloud infrastructure are here discussed, together with the solution designed and implemented in order to monitor the usage of MIDAS services and resources. Also, the strategy adopted to provide the MIDAS platform with the management of elastic resources is outlined.